A Critical Textual Analysis of Immigration Echoes in Moroccan Football Ultras Discourse - EL Hadifi, Mohammed (International Journal of Language and Literary Studies, 2024)
This study seeks to critically analyze the discursive construction of immigration issue within Moroccan football ultras discourse. Through a critical textual analysis as adopted by Norman Fairclough in his three-dimensional approach, the study analyses the seven chosen chants of Moroccan ultras by analyzing the two meta-functions which are posited by Halliday in his SFL which are integrated by Fairclough in the first stage of his model. This study adopts a qualitative approach, concentrating on the experiential, relational, and expressive values of the lexico-grammatical features present in ultras discourse related to immigration. The findings proved that Moroccan football ultras employ a diverse and ideologically charged lexicon. They employ linguistic techniques such as rewording, over-wording, synonymy, hyponymy, and antonymy to articulate immigration complexities. The use of euphemism, dysphemism, and varying formalities enhances emotional engagement. Their deliberate grammatical choices, following Halliday’s transitivity system, convey agency and immigration experiences while avoiding nominalization and negative sentences. Instead, they use direct constructs and positive framing to highlight immigration drivers. Also, the ultras’ discourse reflects multifaceted relational values and asserts their agency within power relations, aligning with Fairclough’s notion of expressive values to engage emotionally and advocate for change in Morocco. The significance of this study resides in its potential to inform policymakers about the critical need to understand the concerns and preoccupations of Moroccan youth, particularly regarding immigration. Thus, policymakers can work more effectively to address and mitigate the underlying causes of this complex phenomenon.